Assessing the sustainability of coconut chain in Sanquianga region, Colombia (2022)
The concept of sustainable development has been widely worked on since its introduction by the Brundtland report (Keeble, 1988), establishing three fundamental pillars: economic viability, social equity, and ecological integrity. Current social and economic imbalances between regions highlight that efforts toward sustainable development must focus on increasing the economic and social conditions in the poorest and emerging economies while encouraging effective practices that generate low environmental damage. Sanquianga, located in south-western Colombia, is an agricultural region in the territories prioritized by the national government for implementing sectoral plans and programs within an integral rural reform framework. These actions intend to mitigate the incidence of armed conflict, poverty, institutional weakness, and the rise of illicit economies, which have historically characterized the socio-economic conditions of this region (EVA, 2017; DANE, 2020). Coconut is a crop culturally rooted in the Sanquianga region and with great economic potential. Nevertheless, its productive chain is weak, mainly because of low-tech farming and insufficient pest control knowledge, where neither machinery, fertilizer, nor pesticide products are used. In addition, no extensive use of the generated outputs is carried out, since only the edible part of the harvested fruit has traditionally been considered valuable output. This study is framed in a two-year project that aims to boost the socioeconomic context of the Sanquianga region by contributing to develop a sustainable coconut supply chain. Specifically, the project evaluates the pre-feasibility of a proposal to create a processing plant for products derived from coconut fruit to make comprehensive use of this commodity (UPV, 2021). As a project deliverable, a report will be carried out. This report aims to be a basis for seeking funding from the government or NGOs to build a coconut processing plant owned by the local community. The prefeasibility evaluation refers to both the evaluation of the technical and legal feasibility, as well as the viability of the three pillars of sustainability. In this study, a preliminary analysis of the current social, economic, and environmental impacts of the coconut production chain in Sanquianga is developed, so that it serves as a basis for establishing the incremental factors of the project proposal compared to the existing one